Contemporary Art on the Touchstone of Social Sciences: The Experience of the Artist Jeff Koons as a Model - Wisam Abdulmawla (Journal of Arts and Social Sciences, 2016)
The current research aims to clarify the overlap of visual arts and contemporary different social sciences. It also aims to re-read the art work in a way to highlight the deep interaction of the recipient with the theme of the artwork in order to establish some art concepts which contribute to change and build a new visual culture for the society. This research also seeks to highlight the importance of today’s contemporary art as one of the fields of science. It dialogues many other areas and intersects with a lot of different sciences including the social sciences as a model for intermediary sciences. It shows the overlap between visual arts and different contemporary social sciences. It seeks, moreover, to re-read the artwork so as to highlight the deep interaction of the recipient with the society’s visual culture. The study tries to consider the idea of crossing borders between the various arts by opening onto each other. In other words, it wishes to emphasize the unique artistic pattern which had been considered to be confined within a unit of specialty with no partnership between one art and another or connection to the social sciences can transcend these borders. The research focuses on the experience of the artist Jeff Koons as a model of the complementary relationship between the practice of fine arts associated with many other fields of specialty, most importantly the social sciences. The research focuses on the experience of the artist as a model for the relationship of complementarily between fine practice and numerous other areas, notably the social sciences.